Pengembangan Ekonomi Masyarakat Melalui Program Diversifikasi Olahan Makanan Berbahan Dasar Jagung di Desa Mategal Kecamatan Parang Kabupaten Magetan - Umi Hanifah; Puji Alawiyah; Aulia Agustin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Assistance to the community of Mategal Village through the management of sweet corn aims to improve the economic quality of the community of Mategal Village, Parang District, Magetan Regency. Assistance uses the Asset Based Community Development (ABCD) approach, which is assistance through the use of village assets to realize the dreams of the assisted communities. This research was conducted more or less one. The assistance activities began with an effort to make the community aware of their village assets which had so far been neglected, even though the village's potential was huge and could be developed. Through a Focus Group Discussion with village officials and members of the PKK, as well as members of the youth group, researchers assisted the community in developing assets through a corn processed diversification program. The planned program has run well and systematically, and the activities take place according to the planned time limit Assistance through the ABCD approach is expected to be able to bring long-term changes for the community in improving the community's economy and provide great benefits for the villagers. Mategal even for the wider community.